Kebijakan Kriminal Pertanggungjawaban Pidana Terhadap Anak Korban Konten Pornografi - Nadhya Puti Lenggo Geni; Alpi Sahari; Ahmad Fauzi (Journal Recht (JR), 2022)
Cases of children as victims of pornographic content have occurred in Surabaya, which has disturbed manyparties. The perpetrators of the distribution of pornographic content are then subject to imprisonment. Childrenas victims of pornographic content should actually be considered more than the perpetrators. Therefore thePolice PPA unit must be able to provide protection for the child. This research is a normative legal research,which is descriptive in nature, with the source of the data used is secondary data sources, data collectiontechniques through literature study, and analyzed with qualitative analysis. Based on the results of the study itwas found that the perspective of the ITE Law, against the existence of pornographic content involving childrenviolated Article 27 paragraph (1) of the ITE Law because it helped spread pornographic content so that it couldbe seen by the wider community. Article 4 paragraph (1) of Law Number 44 Year 2008 concerning Pornographyclearly prohibits child pornography. Article 52 of the ITE Law states that criminal offenses involving decencyor sexual exploitation of children are subject to burdens such as those of the principal crime. Whereas thecriminal policy carried out by the Medan PPA Polrestabes Unit in handling cases of child victims ofpornographic content is by applying Government Regulation Number 40 of 2011 concerning Development,Assistance, and Recovery Against Children who are Victims or Perpetrators of Pornography, namely restoringthe rights of children who are victims .